Depressive symptoms moderate the relationship between sleep quality and cognitive functions among the elderly. Issue 10 (25th November 2016) - Yu, Junhong; Rawtaer, Iris; Mahendran, Rathi; Collinson, Simon L.; Kua, Ee-Heok; Feng, Lei
ABSTRACT: Objective : The co-occurrence of sleep problems, cognitive impairment, and depression among the elderly suggests that these three conditions are likely to be interrelated. Recent findings suggest that depressive symptoms moderate the relationship between sleep problems and cognitive impairment in elderly people but methodological problems have led to inconsistent conclusions. The present study aims to better understand the relationship between sleep quality, depressive symptoms, and cognitive function. Method : We administered the Repeatable Battery for the Assessment of Neuropsychological Status and self-report measures of sleep quality and depression to 380 elderly participants ( M age = 68 years, SD = 5.7). Bootstrapped moderation analyses were conducted to examine the role of depressive symptoms in the relationship between sleep and various aspects of cognitive function. Results : This moderation effect was significant in the domains of delayed memory ( ΔR 2 = .01, F = 4.5, p = .04), language ( ΔR 2 = .01, F = 4.6, p = .035), and general cognitive status ( ΔR 2 = .01, F = 5.3, p = .02). However, unlike previous studies, higher sleep quality corresponded to better outcomes in delayed memory, language abilities, and general cognitive status in participants with low levels of depressive symptoms. No significant relationship between sleep quality and any cognitive function was observed among participants with high levels of depressive symptoms. Conclusions : Among individuals who reported low levels of depressive symptoms, sleep quality was positively related to cognitive performance in the domains of delayed recall, language, and general cognitive status. However, sleep quality was not significantly associated with cognitive abilities in these domains among participants with elevated levels of depressive symptoms; participants had relatively poor outcomes in these cognitive domains regardless of their sleep quality.